Distance and Velocity Characterizations Through Sampling Rate-Limited Main Interferometer in a Silicon Platform - Ting-Qing Liao; Ting-Chia Chang; Jhih-Jia Kang; Shih-Hsiang Hsu (IEEE Photonics Journal)
The Hilbert transform can resample the signal to compensate for the nonlinear frequency sweeping phenomenon and precisely measure a distance and velocity through frequency-modulated continuous-wave (FMCW). Instead of an additional auxiliary interferometer, the direct Hilbert-transform resampling on the main interferograms of a silicon platform could correct the optical-source phase error to form compact light detection and ranging (LiDAR) systems in the characterizations of distances and velocities. More than two samples in an interferogram period will be a criterion in the sampling rate-limited FMCW distance tests. 876.86 cm and 18.058 cm ranging limits are demonstrated through 5 × 105 and 1x104 samples per second from the data acquisition, respectively, in a process-insensitive Mach-Zehnder directional coupler for FMCW-based LiDAR applications. The velocity of 200 mm per second was also illustrated in 5 × 105 samples per second. Moreover, the Hilbert-transform resampled on the main interferometer is superior to the peak-valley approach in the resampling data points, ranging accuracy, and low noise.